The Role of Stimulus and Attentional Factors in the Human Optokinetic Response - Williams, Kirsten G. E. (2025)
The optokinetic response (OKR) is a type of eye movement that plays an essential role in the stabilisation of visual perception. Many studies have investigated the possibility of using the OKR as an objective ‘no-report’ measure of visual function in both clinical and research settings. However, a greater understanding of the OKR (and its components) and how measures are impacted by various top-down and bottom-up factors is an essential first step for the effective application of OKR as an objective tool. To this end, a series of eye movement studies were carried out to quantify the role of stimulus velocity, motion direction, stimulus eccentricity, instruction type, visual attention and the presence of incongruent motion on the OKR in response to drifting sinusoidal luminance gratings (Experiment 1) and random-dot kinematograms (Experiment 2 and Experiment 3). In Experiment 1, stimulus velocity, motion di-rection and instruction type (look/stare) were manipulated; results indicated that increasing stimulus velocity and direction of motion away from the horizontal axis reduced the gain of the OKR. Further, reversed OKAN direction was associated with low accuracy of the preceding OKR (low gain and directional inaccuracy), indicating that this reversal may have been caused by adaptation to visual motion during optokinetic stimulation. In Experiment 2, central and peripheral regions of the visual field were stimulated separately and simultaneously with opposing directions of motion, while visual attention was manipulated. This revealed a generalised attentional boost to OKR gain and a crucial role for foveal stimulation in driving high-fidelity OKR. In the absence of central stimulation, increasing peripheral stimulus area did not increase gain. Importantly, generating an OKR to peripheral stimulation was possible in the presence of a central stimulus moving in the opposite direction, when attention was directed to the periphery. This points to an attentional reweighting of the relative contributions of different spatial regions when generating the OKR. Finally, Experiment 3 presented discrete patches of motion stimuli to 27 different spatial locations of the visual field while varying direction of motion and manipulating attention. The results were used to develop detailed maps of OKR gain across the visual field. The data presented in this thesis highlight how OKR is influenced by a wide variety of endogenous and exogenous factors that must be carefully considered in the development of OKR-based objective measures.